Design, Validation and CFD Modeling of an Environmental Wind Tunnel - Francesco Pinna; Battista Grosso; Alessio Lai; Ouiza Bouarour; Cristiano Armas; Maurizio Serci; Valentina Dentoni (Atmosphere, 2024)
The wind erosion of granular materials stored within the open yards of industrial plants (i.e., industrial wind erosion) and the subsequent emission and dispersion of particulate matter (PM) in the surrounding areas represent an important issue for the exposed population and for the environment as a whole. The Environment Impact Assessment (EIA) and the design of emission control measures require a deep knowledge of the erosion phenomenon, and the precise estimation of the Emission Factors (EF) associated with the specific PM source under investigation. Aiming to characterize the emission potential of industrial granular materials, a new Environmental Wind Tunnel (EWT) has recently been built at the Department of Civil and Environmental Engineering and Architecture (DICAAR) laboratories, in Cagliari University. The article discusses the EWT’s updated design and the set-up methodologies applied to reproduce the Atmospheric Boundary Layer (ABL) acting over the surfaces of coarse and heterogeneous granular materials. In addition, a Computational Fluid Dynamics (CFD) model of the EWT has been developed to reproduce and analyze the wind field throughout the entire tunnel volume and preliminarily evaluate possible modifications to the original design. The accuracy of the simulation has been verified by comparing the CFD model and the results of the experimental tests.